Preparation method of titanium alloy surface DLC coating

By performing laser polishing and laser texture treatment in a nitrogen atmosphere, the problem of hardness mismatch between the surface of the titanium alloy and the DLC coating is solved, and a transition layer with moderate hardness and mechanical fit structure are realized, which significantly improves binding force and durability.

CN119710537AActive Publication Date: 2025-03-28HENAN MECHANICAL & ELECTRICAL VOCATIONAL COLLEGE
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411985398.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

There is a problem of hardness mismatch between the surface of the titanium alloy and the DLC coating, which leads to insufficient binding force, which easily leads to stress concentration when external forces or temperature changes, weakens the binding force and makes the DLC coating easy to peel off.

Method used

Laser polishing is performed in a nitrogen atmosphere to achieve grain refinement on the surface of the titanium alloy and the generation of TiN crystals, providing a transition layer with moderate hardness to alleviate the poor hardness. At the same time, the contact area between the DLC coating and the titanium alloy substrate is increased by laser texture treatment, forming a mechanically fitted structure and enhancing adhesion.

Benefits of technology

It effectively improves the bonding force between the DLC coating and the titanium alloy substrate, reduces stress differences and stress concentration, and enhances the adhesion and durability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710537A_ABST
    Figure CN119710537A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metal surface treatment, and discloses a titanium alloy surface DLC coating preparation method which comprises the steps of titanium alloy substrate cleaning and drying, laser polishing treatment, laser texture treatment, deburring treatment, DLC coating deposition and the like. According to the method, laser polishing treatment is carried out in the nitrogen atmosphere, grain refinement on the surface of the titanium alloy and generation of TiN crystals are achieved, a transition layer with moderate hardness is provided for the DLC coating, the hardness difference between the titanium alloy and the DLC coating is relieved, the stress difference and stress concentration phenomena generated when external force or temperature changes are reduced, and the binding force is enhanced; meanwhile, the contact area of the DLC coating and the titanium alloy substrate is increased through a microstructure generated through laser texturing treatment, a mechanical embedded structure is formed, and the adhesive force of the DLC coating is further enhanced; therefore, the binding force between the DLC coating and the titanium alloy substrate can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of metal surface treatment, and in particular to a method for preparing a DLC coating on a titanium alloy surface. Background Art

[0002] Titanium alloys have been widely used in aerospace, marine, biomedical, automotive and transportation fields due to their high specific strength, corrosion resistance, excellent biocompatibility and many other excellent properties. In practical applications, titanium alloy parts often need to have their surface properties optimized before use. Among many surface treatment technologies, depositing diamond-like carbon (DLC) coating on the surface of titanium alloy is an effective means to improve its surface properties. DLC coating has the advantages of high hardness, low friction coefficient, good wear resistance and corrosion resistance, and can significantly improve the performance of titanium alloy parts during use, such as extending service life and improving work efficiency.

[0003] However, the hardness of titanium alloy itself is relatively low (generally the hardness does not exceed about 350HV), while the hardness of DLC coating is relatively high, which can reach more than 1500HV. This large hardness difference causes a serious hardness mismatch at the interface between the titanium alloy surface and the DLC coating. When subjected to external impact or undergoing thermal expansion and contraction due to temperature changes, due to the different deformation capabilities of the two materials, the high-hardness DLC layer deforms relatively less, while the low-hardness titanium alloy deforms relatively more, which will form a large stress difference at the interface. This stress difference will produce a great stress concentration phenomenon at the interface, which will seriously weaken the bonding force and make the DLC coating easy to peel off from the titanium alloy surface.

[0004] Traditional coating deposition methods often simply deposit DLC coatings on the surface of titanium alloys without fully considering how to fundamentally enhance the bonding between the two. It is far from enough to rely solely on the physical adsorption between the coating and the substrate material. Under actual working conditions, this weak bonding method is difficult to withstand the influence of various complex external forces, thermal stress and other factors.

[0005] Therefore, it is necessary to find a method for preparing a DLC coating on a titanium alloy surface that can effectively improve the bonding force between the DLC coating and the titanium alloy substrate. Summary of the invention

[0006] The purpose of the present application is to provide a method for preparing a DLC coating on a titanium alloy surface, which can effectively improve the bonding strength between the DLC coating and the titanium alloy substrate.

[0007] The present application provides a method for preparing a DLC coating on a titanium alloy surface, comprising the steps of: A1. Clean and dry the titanium alloy substrate; A2. laser polishing the surface of the titanium alloy substrate to be processed in a nitrogen atmosphere to cause grain refinement and generate TiN crystals on the surface to be processed; A3. Performing laser texturing on the surface to be processed; A4. Deburring the surface to be processed; A5. Use PVD technology to deposit DLC coating on the surface to be processed.

[0008] This method achieves grain refinement and TiN crystal generation on the surface of titanium alloy by laser polishing in nitrogen atmosphere, provides a transition layer with moderate hardness for DLC coating, alleviates the hardness difference between titanium alloy and DLC coating, reduces stress difference and stress concentration caused by external force or temperature change, and enhances bonding strength. At the same time, the microstructure generated by laser texturing increases the contact area between DLC coating and titanium alloy substrate, forms a mechanical interlocking structure, and further enhances the adhesion of DLC coating; therefore, it can effectively improve the bonding strength between DLC coating and titanium alloy substrate.

[0009] Preferably, step A2 comprises: A201. A continuous laser is used in a nitrogen atmosphere to perform a rough polishing treatment on the surface of the titanium alloy substrate to be processed, so that the grain refinement of the surface to be processed occurs and TiN crystals are generated; A202. Fine polishing the surface to be processed after rough polishing using a nanosecond pulse laser in a nitrogen atmosphere to further reduce the roughness of the surface to be processed; A203. Detect the mass percentage of each chemical element in the surface to be processed by EDS technology, and when the mass percentage of N is not greater than the mass percentage of O, execute step A202 again; when the mass percentage of N is greater than the mass percentage of O, end the laser polishing process.

[0010] Through the step-by-step laser polishing process, combined with real-time element detection and feedback mechanism, the technical problems of grain refinement and TiN crystal formation during laser polishing of titanium alloy surface were effectively solved. First, a continuous laser was used for rough polishing in a nitrogen atmosphere to achieve surface grain refinement and preliminary formation of TiN crystals. Then, a nanosecond pulsed laser was used for fine polishing to further reduce the surface roughness. Finally, the surface element composition was detected by EDS technology, and the decision on whether to continue fine polishing was made based on the mass percentage of N and O, ensuring the sufficient formation of TiN crystals.

[0011] Preferably, in step A201, when using a continuous laser to rough-polish the surface to be processed of the titanium alloy substrate, the laser power is set to 500W-700W, the scanning speed is set to 1000mm / s-1200mm / s, the scanning interval is set to 0.03mm-0.05mm, the defocus amount is set to 2mm, and the spot diameter is set to 0.2mm-0.3mm.

[0012] Preferably, in step A202, when a nanosecond pulse laser is used to fine-polish the surface to be processed after rough polishing, the laser power is set to 80W-100W, the pulse width is set to 15ns, the repetition frequency is set to 80KHz-120KHz, the scanning speed is set to 3000mm / s-4000mm / s, the scanning interval is set to 0.015mm-0.03mm, and the spot diameter is set to 0.1mm-0.2mm.

[0013] Preferably, step A3 comprises: A nanosecond pulse laser is used to perform laser texturing on the surface to be processed.

[0014] The use of nanosecond pulsed lasers enables precise control and processing of the titanium alloy surface. The nanosecond pulse width can release energy in a very short time, thereby forming a specific microstructure on the titanium alloy surface without significantly affecting the overall performance of the material.

[0015] Preferably, when using a nanosecond pulse laser to perform laser texturing on the surface to be processed, the laser power is set to 20W-60W, the pulse width is set to 150ns, the repetition frequency is set to 40KHz-70KHz, the scanning speed is set to 200mm / s-700mm / s, and the spot diameter is set to 80μm-200μm.

[0016] Preferably, when the surface to be processed is subjected to laser texturing using a nanosecond pulse laser, the area of ​​the laser texturing pattern on the surface to be processed accounts for 5%-90%.

[0017] Preferably, step A4 comprises: The surface to be processed is finely polished using 800-1200 mesh diamond sandpaper to remove burrs, and the friction coefficient between the diamond sandpaper and the surface to be processed is detected in real time during the fine polishing process until the friction coefficient drops to a stable level, and then the deburring process is stopped.

[0018] Preferably, step A5 comprises: A501. Ar ion bombardment of the surface to be processed in the vacuum chamber of the PVD equipment; A502. Deposit a DLC coating on the surface to be processed in the vacuum chamber of a PVD device.

[0019] Preferably, the titanium alloy substrate is made of TC4 titanium alloy.

[0020] Beneficial effects: The preparation method of the DLC coating on the surface of a titanium alloy provided in the present application comprises the steps of cleaning and drying the titanium alloy substrate, laser polishing, laser texturing, deburring and depositing the DLC coating; by performing laser polishing in a nitrogen atmosphere, grain refinement and the generation of TiN crystals on the surface of the titanium alloy are achieved, providing a transition layer with moderate hardness for the DLC coating, alleviating the hardness difference between the titanium alloy and the DLC coating, reducing the stress difference and stress concentration caused by external force or temperature changes, and enhancing the bonding strength; at the same time, the microstructure generated by the laser texturing treatment increases the contact area between the DLC coating and the titanium alloy substrate, and forms a mechanical interlocking structure, further enhancing the adhesion of the DLC coating; therefore, the bonding strength between the DLC coating and the titanium alloy substrate can be effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Flow chart of the method for preparing DLC ​​coating on the surface of titanium alloy provided in an embodiment of the present application. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present application provided in the drawings is not intended to limit the scope of the application claimed for protection, but merely represents the selected embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application.

[0023] It should be noted that similar reference numerals and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further defined and explained in subsequent drawings. At the same time, in the description of this application, the terms "first", "second", etc. are only used to distinguish the description and cannot be understood as indicating or implying relative importance.

[0024] Depositing DLC ​​coating on the surface of titanium alloy is an effective method to improve its surface properties. However, due to the large hardness difference between titanium alloy and DLC coating, the bonding between the two is weak. Specifically, the hardness of titanium alloy usually does not exceed 350HV, while the hardness of DLC coating can reach more than 1500HV. This hardness mismatch will cause severe stress concentration at the interface, making the DLC coating easy to peel off from the surface of titanium alloy. Traditional coating deposition methods often simply deposit DLC coating on the surface of titanium alloy without fully considering how to fundamentally enhance the bonding between the two. The bonding method that relies solely on physical adsorption is difficult to withstand the influence of various complex external forces and thermal stresses, which seriously affects the durability and reliability of the coating.

[0025] In order to solve the problem of insufficient bonding strength between the DLC coating and the titanium alloy substrate, the present application provides an innovative method for preparing the DLC coating on the surface of a titanium alloy.

[0026] Please refer to Figure 1 In some embodiments of the present application, a method for preparing a DLC coating on a titanium alloy surface comprises the steps of: A1. Clean and dry the titanium alloy substrate; A2. laser polishing the surface of the titanium alloy substrate to be processed in a nitrogen atmosphere to cause grain refinement and generate TiN crystals on the surface to be processed; A3. Laser texturing of the surface to be processed; A4. Deburr the surface to be processed; A5. Use PVD (Physical Vapor Deposition) technology to deposit DLC coating on the surface to be processed.

[0027] This method achieves grain refinement and TiN crystal generation on the surface of titanium alloy by laser polishing in nitrogen atmosphere, provides a transition layer with moderate hardness for DLC coating, alleviates the hardness difference between titanium alloy and DLC coating, reduces stress difference and stress concentration caused by external force or temperature change, and enhances bonding strength. At the same time, the microstructure generated by laser texturing increases the contact area between DLC coating and titanium alloy substrate, forms a mechanical interlocking structure, and further enhances the adhesion of DLC coating; therefore, it can effectively improve the bonding strength between DLC coating and titanium alloy substrate.

[0028] Specifically, first, the titanium alloy substrate is cleaned and dried to remove dirt and moisture on the surface, providing a clean surface to be processed for subsequent processing. Then, laser polishing is performed in a nitrogen atmosphere. The thermal effect of the laser beam causes the surface material to be processed to remelt and resolidify, resulting in grain refinement (refined grains reduce the number of grain boundaries and increase dislocation density. At the same time, grain boundaries can effectively hinder dislocation movement, thereby enhancing the material's ability to resist deformation and strengthen the material's hardness, thereby reducing the hardness difference between the titanium alloy substrate surface and the DLC coating). At the same time, in a nitrogen atmosphere, titanium atoms react with nitrogen atoms to generate TiN crystals (TiN crystals have a large hardness, which can further reduce the hardness difference between the titanium alloy substrate surface and the DLC coating). This process not only improves the roughness of the surface to be processed, but also forms a TiN transition layer with moderate hardness. Next, laser texturing is performed, which uses a pulsed laser to create a microstructure on the surface to be processed. By controlling parameters such as laser power, pulse width, and repetition frequency, specific micro-morphologies such as micro-pits and micro-grooves can be formed on the surface to be processed. These microstructures increase the surface area and provide more mechanical engagement points. Subsequently, deburring is performed to remove tiny protrusions on the surface to be processed (including burrs that may be generated during laser texturing). This step further improves the surface quality of the surface to be processed and creates conditions for the uniform deposition of the DLC coating. Finally, the DLC coating is deposited using PVD technology to obtain the finished product.

[0029] The cleaning process refers to the removal of dirt, grease and other impurities on the surface of the titanium alloy substrate, which can be achieved by ultrasonic cleaning or chemical cleaning. The drying process refers to the removal of moisture on the surface of the titanium alloy substrate, which can be achieved by oven or hot air drying.

[0030] In some possible implementations, step A1 includes: A101. Immerse the titanium alloy substrate in anhydrous ethanol solution for ultrasonic cleaning for 10 minutes; A102. The titanium alloy substrate was immersed in deionized water for ultrasonic cleaning for 10 minutes; A103. Dry the titanium alloy substrate.

[0031] Among them, laser polishing refers to using a laser beam to scan the surface of the titanium alloy substrate, causing the surface material to remelt and resolidify through thermal effects. It can be achieved specifically by using a continuous laser or a pulsed laser.

[0032] In some preferred embodiments, step A2 comprises: A201. A continuous laser is used in a nitrogen atmosphere to perform rough polishing on the surface of a titanium alloy substrate to be processed, so that grain refinement occurs on the surface to be processed and TiN crystals are generated; A202. Fine polishing the surface to be processed after rough polishing using a nanosecond pulse laser in a nitrogen atmosphere to further reduce the roughness of the surface to be processed; A203. Detect the mass percentage of each chemical element in the surface to be processed by EDS (Energy Dispersive Spectroscopy) technology, and when the mass percentage of N is not greater than the mass percentage of O, execute step A202 again. When the mass percentage of N is greater than the mass percentage of O, end the laser polishing process.

[0033] Through the step-by-step laser polishing process, combined with real-time element detection and feedback mechanism, the technical problems of grain refinement and TiN crystal formation during laser polishing of titanium alloy surface were effectively solved. First, a continuous laser was used for rough polishing in a nitrogen atmosphere to achieve surface grain refinement and preliminary formation of TiN crystals. Then, a nanosecond pulsed laser was used for fine polishing to further reduce the surface roughness. Finally, the surface element composition was detected by EDS technology, and the decision on whether to continue fine polishing was made based on the mass percentage of N and O, ensuring the sufficient formation of TiN crystals.

[0034] Specifically, laser polishing is carried out in a nitrogen atmosphere: this provides the necessary nitrogen source for the growth of TiN crystals while also preventing the titanium alloy surface from being oxidized.

[0035] Use continuous laser for rough polishing: Continuous laser can provide continuous high energy input, which is beneficial to the grain refinement and generation of TiN crystals on the surface of titanium alloy.

[0036] Fine polishing with nanosecond pulsed lasers: Nanosecond pulsed lasers can provide more precise energy control, helping to further reduce surface roughness without destroying the formed TiN crystals.

[0037] Detect the surface element composition through EDS technology: This can accurately determine the formation of TiN crystals and ensure the effect of polishing. EDS detection can be carried out after each fine polishing, and the detection area can select multiple representative positions of the surface to be processed.

[0038] The decision to continue fine polishing is based on the comparison of the mass percentages of N and O: this ensures the adequate generation of TiN crystals while avoiding the negative effects that may be caused by over-polishing. When the mass percentage of N is greater than the mass percentage of O, it can be considered that TiN crystals have been fully generated and the laser polishing process can be terminated.

[0039] Preferably, in step A201, when using a continuous laser to rough-polish the surface to be processed of the titanium alloy substrate, the laser power is set to 500W-700W, the scanning speed is set to 1000mm / s-1200mm / s, the scanning interval is set to 0.03mm-0.05mm, the defocus amount is set to 2mm, and the spot diameter is set to 0.2mm-0.3mm.

[0040] Specifically, the power of the continuous laser in this application is set to 500W-700W, and this power range can ensure sufficient energy input to promote the reorganization and grain refinement of the surface material. When the power is lower than 500W, it may not provide enough energy to achieve effective surface treatment; when the power exceeds 700W, it may cause the surface to overheat, resulting in unnecessary material loss or surface deformation. The scanning speed is set to 1000mm / s-1200mm / s, and this speed range can effectively control the action time of the laser on the surface and balance the treatment effect and efficiency. If the scanning speed is too slow, local overheating may occur; if the speed is too fast, the expected treatment effect may not be achieved. The scanning interval is set to 0.03mm-0.05mm, which ensures that the entire surface is evenly treated to avoid omissions or repetitions. Too large an interval may cause some areas to be untreated, while too small an interval may cause unnecessary energy waste and extended processing time. The defocus is set to 2mm, and the setting of this parameter helps to adjust the laser energy density and optimize the treatment effect. Through appropriate defocusing, the energy distribution of the laser on the surface can be controlled to avoid material damage caused by excessive local energy concentration. The spot diameter is set to 0.2mm-0.3mm. This range can effectively control the single treatment area and affect the energy distribution and treatment accuracy. A smaller spot can improve the treatment accuracy, but may increase the treatment time; a larger spot can improve efficiency, but may reduce the accuracy.

[0041] By properly controlling the laser power, scanning speed, scanning interval and other parameters, the titanium alloy substrate surface can be effectively rough-polished in a nitrogen atmosphere. This process can not only reduce the surface roughness (the roughness Sa value can be reduced to less than 2μm), but also promote grain refinement and the formation of TiN crystals, laying the foundation for subsequent fine polishing and DLC coating deposition. The rough polishing treatment through the above steps can make the hardness of the processed surface reach 900HV-1000HV, which is less than the hardness deviation of the DLC coating.

[0042] Preferably, in step A202, when using a nanosecond pulse laser to fine-polish the surface to be processed after rough polishing, the laser power is set to 80W-100W, the pulse width is set to 15ns, the repetition frequency is set to 80KHz-120KHz, the scanning speed is set to 3000mm / s-4000mm / s, the scanning interval is set to 0.015mm-0.03mm, and the spot diameter is set to 0.1mm-0.2mm.

[0043] Specifically, the nanosecond pulse laser used can provide extremely short pulses, which is conducive to fine control of heat input and reduction of heat-affected zone. The laser power is set to 80W-100W. This appropriate power range can ensure sufficient energy for surface treatment without excessive heating and surface damage. The pulse width is set to 15ns. This extremely short pulse width can reduce the heat accumulation effect and facilitate more refined surface treatment. The repetition frequency is set to 80KHz-120KHz. A higher repetition frequency can improve processing efficiency while ensuring sufficient energy density. The scanning speed is set to 3000mm / s-4000mm / s. This higher scanning speed can reduce single-point heat accumulation and facilitate uniform surface treatment. The scanning interval is set to 0.015mm-0.03mm. A smaller scanning interval can ensure that the surface is evenly treated to avoid omissions. The spot diameter is set to 0.1mm-0.2mm. A smaller spot diameter can increase the energy density and facilitate fine treatment.

[0044] By using nanosecond pulse lasers and precisely controlling parameters such as laser power, pulse width, repetition frequency, scanning speed, scanning interval and spot diameter, the surface roughness can be further reduced on the basis of rough polishing (the roughness Sa value can be reduced to below 0.5μm), providing a better foundation for the subsequent deposition of DLC coatings.

[0045] Among them, laser texturing refers to the use of a laser beam to create a microstructure on the surface of a titanium alloy substrate. It can be achieved by using a pulsed laser to form a specific surface morphology by controlling the laser parameters.

[0046] In some possible implementations, step A3 includes: Nanosecond pulsed laser is used to perform laser texturing on the surface to be processed.

[0047] The use of nanosecond pulsed lasers enables precise control and processing of titanium alloy surfaces. Nanosecond pulse widths can release energy in a very short period of time, thereby forming a specific microstructure on the surface to be processed without significantly affecting the overall performance of the material.

[0048] Preferably, when using a nanosecond pulse laser to perform laser texturing on the surface to be processed, the laser power is set to 20W-60W, the pulse width is set to 150ns, the repetition frequency is set to 40KHz-70KHz, the scanning speed is set to 200mm / s-700mm / s, and the spot diameter is set to 80μm-200μm.

[0049] Specifically, the laser power is set in the range of 20W-60W to ensure sufficient energy for surface modification without excessively damaging the substrate. The pulse width of 150ns can provide high peak power in a short time, which is conducive to the formation of surface microstructures. The repetition frequency is set to 40KHz-70KHz to ensure sufficient pulse overlap rate, which is conducive to the formation of uniform surface structure. The scanning speed is set to 200mm / s-700mm / s to match the repetition frequency, which can control the energy input per unit area. The spot diameter is set to 80μm-200μm, which determines the size range of the microstructure. This range can make the steepness of the pits or grooves textured by the laser on the titanium alloy surface less than 45 degrees, which is more conducive to improving the bonding force between the DLC coating and the surface to be processed. The settings of these parameters are interrelated and work together to achieve the ideal laser texturing effect. For example, the combination of power and pulse width determines the energy of a single pulse, while the combination of repetition frequency and scanning speed affects the distribution density of energy on the surface. The spot diameter directly affects the size and morphology of the microstructure.

[0050] Furthermore, when the surface to be processed is subjected to laser texturing using a nanosecond pulse laser, the area of ​​the laser texturing pattern on the surface to be processed is 5%-90%.

[0051] Specifically, when the area of ​​the laser texturing pattern accounts for no less than 5%, it can ensure that sufficient microstructures are formed on the surface to be processed, effectively enhancing the adhesion of the subsequent DLC coating. This is because the surface to be processed after texturing will form a micro-scale concave-convex structure, which increases the effective contact area of ​​the surface to be processed, thereby increasing the mechanical bite force between the DLC coating and the surface to be processed. On the other hand, when the area of ​​the laser texturing pattern accounts for no more than 90%, a certain proportion of the original surface can be retained to avoid excessive texturing leading to a decrease in matrix strength. Excessive texturing treatment may destroy the integrity of the surface and affect the mechanical properties of the titanium alloy substrate. By limiting the texture area, a balance can be achieved between enhancing coating adhesion and maintaining substrate strength.

[0052] The laser texturing pattern may be, but is not limited to, a line array pattern, a dot array pattern, a grid pattern, or an array of graphics (such as circular, triangular, diamond, trapezoidal, etc. graphics).

[0053] Deburring refers to removing tiny protrusions on the surface of the titanium alloy substrate, which can be achieved by mechanical polishing or chemical polishing.

[0054] In some possible implementations, step A4 includes: Use 800-1200 mesh diamond sandpaper to fine-polish the surface to be processed to remove burrs, and detect the friction coefficient between the diamond sandpaper and the surface to be processed in real time during the fine-polishing process. Stop the deburring process until the friction coefficient drops to a stable level.

[0055] Diamond sandpaper with a mesh of 800-1200 has a moderate abrasive size and can effectively remove surface burrs without causing excessive damage to the surface. Sandpaper with a lower mesh number may cause surface scratches, while sandpaper with a higher mesh number may not be able to effectively remove burrs. During the fine polishing process, the friction coefficient between the diamond sandpaper and the surface to be processed is detected in real time. By monitoring the change in the friction coefficient, the effect of the deburring treatment can be judged. As the surface burrs are gradually removed, the friction coefficient will gradually decrease. When the friction coefficient drops to a stable level, stop the deburring treatment. This judgment standard can ensure the adequacy and effectiveness of the deburring treatment and avoid excessive grinding to damage the textured surface. The stability of the friction coefficient indicates that the surface has achieved the ideal deburring effect, and continued treatment may cause unnecessary material loss. These technical features can cooperate with each other to achieve effective deburring of the titanium alloy surface and provide good surface conditions for the subsequent deposition of DLC coating.

[0056] Among them, a friction sensor can be arranged at the mechanical polishing disk for installing the diamond sandpaper, so as to realize real-time detection of the friction coefficient between the diamond sandpaper and the surface to be processed during the fine polishing process.

[0057] Among them, PVD technology refers to physical vapor deposition technology, and specifically, magnetron sputtering, ion plating or arc ion plating and other methods can be used to achieve the deposition of DLC coating.

[0058] In some possible implementations, step A5 includes: A501. Ar ion bombardment of the surface to be processed in the vacuum chamber of the PVD equipment; A502. Deposit DLC coating on the surface to be processed in the vacuum chamber of the PVD equipment.

[0059] Ar ion bombardment can clean and activate the surface to be processed, creating good interface conditions for the deposition of DLC coating. During the deposition of DLC coating, the structure and performance of DLC coating can be regulated by controlling parameters such as vacuum chamber temperature, gas flow, hot wire current and substrate bias, thereby improving the bonding strength between DLC coating and titanium alloy substrate.

[0060] Preferably, in step A501, the surface to be processed is bombarded for 15 minutes to 60 minutes under the following conditions: the temperature of the vacuum chamber is set to 180°C to 300°C, and argon gas with a gas flow rate of 150sccm to 300sccm is introduced into the vacuum chamber, the negative bias voltage of the titanium alloy substrate is set to 50V to 150V, and the bias duty cycle is set to 40% to 60%.

[0061] During the Ar ion bombardment process, the vacuum chamber temperature is set at 180°C to 300°C to ensure that the titanium alloy substrate surface is sufficiently active while avoiding deformation of the substrate caused by excessive temperature. The argon flow rate is controlled at 150sccm to 300sccm to provide an appropriate amount of Ar ions for surface bombardment, which can effectively clean the surface without causing excessive damage to the substrate. The negative bias voltage of the titanium alloy substrate is set to 50V to 150V and the bias duty cycle is 40% to 60%, which can control the energy and bombardment frequency of the Ar ions, thereby optimizing the surface cleaning and activation effects.

[0062] Preferably, in step A502, DLC coating deposition is performed on the surface to be processed for a duration of 1 hour to 4 hours under the following conditions: the temperature of the vacuum chamber is set to 180°C to 300°C, and argon gas with a gas flow rate of 120sccm to 250sccm and acetylene with a gas flow rate of 200sccm to 400sccm are introduced into the vacuum chamber, the hot wire current is set to 10A to 80A, the negative bias voltage of the titanium alloy substrate is set to 650V to 950V, and the bias duty cycle is set to 20% to 80%.

[0063] During the deposition of the DLC coating, the vacuum chamber temperature is maintained at 180°C to 300°C to ensure the stability of the coating growth. The flow rates of argon and acetylene are controlled at 120sccm to 250sccm and 200sccm to 400sccm, respectively, which can adjust the composition and structure of the DLC coating. The hot wire current is set to 10A to 80A, which affects the decomposition efficiency of the carbon source, and thus affects the growth rate and quality of the coating. The negative bias voltage of the titanium alloy substrate is set to 650V to 950V and the bias duty cycle is 20% to 80%, which can control the ion bombardment energy and frequency, thereby affecting the density and internal stress of the coating. The coordination of these parameters can achieve a gradual transition between the DLC coating and the titanium alloy substrate, reduce interfacial stress, and improve bonding strength. For example, by adjusting the ratio of acetylene and argon, a titanium-rich carbide transition layer can be formed at the interface, further enhancing the bonding between the coating and the substrate.

[0064] In addition, based on the above conditions, the DLC coating is deposited for 1 hour to 4 hours, and the surface of the DLC coating obtained has a micro-depression structure corresponding to the laser texturing pattern. If the titanium alloy substrate is oil-lubricated when used, this micro-depression structure provides a dynamic pressure effect for the good containment and uniform distribution of the lubricating oil. Coupled with the strengthening of the surface by TiN crystals, the lubricating oil forms a stable oil film, which greatly reduces the friction coefficient.

[0065] Among them, the material of the titanium alloy substrate can be selected according to actual needs. Preferably, the material of the titanium alloy substrate is TC4 titanium alloy. TC4 titanium alloy has high strength and low density, which makes the prepared DLC coating have good mechanical performance support. Secondly, TC4 titanium alloy has excellent corrosion resistance, which complements the corrosion resistance of the DLC coating and further improves the overall corrosion resistance. In addition, TC4 titanium alloy has good biocompatibility, which makes the prepared DLC coating have potential application value in the biomedical field. It should be noted that, according to the test surface, compared with other titanium alloys, the treatment effect of TC4 titanium alloy treated by the above method is the best (the bonding force between the DLC coating and the titanium alloy substrate is the strongest).

[0066] In summary, the method for preparing the DLC coating on the surface of titanium alloy provided in the present application has at least the following advantages: 1. TiN crystals are generated through continuous laser rough polishing to form gradient hardness, which alleviates the hardness difference between titanium alloy and DLC coating, reduces the stress difference and stress concentration caused by external force or temperature change, and enhances the bonding strength; and the microstructure produced by laser texturing increases the contact area and forms a mechanical fit, which closely connects the DLC coating and the titanium alloy substrate like a "mortise and tenon structure", effectively improving the coating-substrate bonding strength; 2. On the surface of the titanium alloy substrate treated by this scheme, the low friction coefficient characteristics of the DLC coating itself combined with the laser texturing microstructure to reduce the actual contact area, and the TiN crystals and gradient hardness structure to optimize the surface performance, jointly reduce the friction coefficient of the titanium alloy substrate surface; under oil lubrication conditions, the lipophilicity of the DLC coating combined with the good containment and uniform distribution of the lubricating oil by the micro-depression structure provides a dynamic pressure effect, and the strengthening of the surface by TiN crystals allows the oil to form a stable oil film, which greatly reduces the friction coefficient.

[0067] In this document, relational terms such as first and second, etc. are used merely to distinguish one entity or operation from another entity or operation, but do not necessarily require or imply any such actual relationship or order between these entities or operations.

[0068] The above description is only an embodiment of the present application and is not intended to limit the protection scope of the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a DLC coating on a titanium alloy surface, characterized in that: Includes steps: A1. Clean and dry the titanium alloy substrate; A2. laser polishing the surface of the titanium alloy substrate to be processed in a nitrogen atmosphere to cause grain refinement and generate TiN crystals on the surface to be processed; A3. Performing laser texturing on the surface to be processed; A4. Deburring the surface to be processed; A5. Use PVD technology to deposit DLC coating on the surface to be processed.

2. The method for preparing a DLC coating on a titanium alloy surface according to claim 1, characterized in that: Step A2 includes: A201. A continuous laser is used in a nitrogen atmosphere to perform a rough polishing treatment on the surface of the titanium alloy substrate to be processed, so that the grain refinement of the surface to be processed occurs and TiN crystals are generated; A202. Fine polishing the surface to be processed after rough polishing using a nanosecond pulse laser in a nitrogen atmosphere to further reduce the roughness of the surface to be processed; A203. Detect the mass percentage of each chemical element in the surface to be processed by EDS technology, and when the mass percentage of N is not greater than the mass percentage of O, execute step A202 again; when the mass percentage of N is greater than the mass percentage of O, end the laser polishing process.

3. The method for preparing a DLC coating on a titanium alloy surface according to claim 2, characterized in that: In step A201, when using a continuous laser to rough-polish the surface to be processed of the titanium alloy substrate, the laser power is set to 500W-700W, the scanning speed is set to 1000mm / s-1200mm / s, the scanning interval is set to 0.03mm-0.05mm, the defocus amount is set to 2mm, and the spot diameter is set to 0.2mm-0.3mm.

4. The method for preparing a DLC coating on a titanium alloy surface according to claim 2, characterized in that: In step A202, when using a nanosecond pulse laser to fine-polish the surface to be processed after rough polishing, the laser power is set to 80W-100W, the pulse width is set to 15ns, the repetition frequency is set to 80KHz-120KHz, the scanning speed is set to 3000mm / s-4000mm / s, the scanning interval is set to 0.015mm-0.03mm, and the spot diameter is set to 0.1mm-0.2mm.

5. The method for preparing a DLC coating on a titanium alloy surface according to claim 1, characterized in that: Step A3 includes: A nanosecond pulse laser is used to perform laser texturing on the surface to be processed.

6. The method for preparing a DLC coating on a titanium alloy surface according to claim 5, characterized in that: When using a nanosecond pulse laser to perform laser texturing on the surface to be processed, the laser power is set to 20W-60W, the pulse width is set to 150ns, the repetition frequency is set to 40KHz-70KHz, the scanning speed is set to 200mm / s-700mm / s, and the spot diameter is set to 80μm-200μm.

7. The method for preparing a DLC coating on a titanium alloy surface according to claim 5, characterized in that: When the surface to be processed is subjected to laser texturing treatment using a nanosecond pulse laser, the area of ​​the laser texturing pattern on the surface to be processed accounts for 5%-90%.

8. The method for preparing a DLC coating on a titanium alloy surface according to claim 1, characterized in that: Step A4 includes: The surface to be processed is finely polished using 800-1200 mesh diamond sandpaper to remove burrs, and the friction coefficient between the diamond sandpaper and the surface to be processed is detected in real time during the fine polishing process until the friction coefficient drops to a stable level, and then the deburring process is stopped.

9. The method for preparing a DLC coating on a titanium alloy surface according to claim 1, characterized in that: Step A5 includes: A501. Ar ion bombardment of the surface to be processed in the vacuum chamber of the PVD equipment; A502. Deposit a DLC coating on the surface to be processed in the vacuum chamber of a PVD device.

10. The method for preparing a DLC coating on a titanium alloy surface according to any one of claims 1 to 9, characterized in that: The material of the titanium alloy substrate is TC4 titanium alloy.

Citation Information

Patent Citations

  • Laser preparation method of titanium-nitride-coating-contained textured surface of titanium alloy

    CN107345289A

  • Ion surface etching method for diamond-like coating before preparing

    CN110735107A

  • Coating material for forming self-lubricating amorphous carbon film based on friction-induced catalysis and preparation method of coating material

    CN111979543A

  • Method for realizing laser zirconium nitride-based amorphous alloy surface planarization through laser polishing

    CN113275740A

  • Using laser for fabricating coatings substrate

    CN1141602A